2015
DOI: 10.1179/2045772315y.0000000047
|View full text |Cite
|
Sign up to set email alerts
|

Spinal 5-HT3 receptor mediates nociceptive effect on central neuropathic pain; possible therapeutic role for tropisetron

Abstract: Objectives: To test the analgesic effect of 5-HT-3 receptor antagonist, tropisetron, in a clip compression injury model of spinal cord pain in rats. Methods: Four weeks post compression of the spinal cord at lumbar level, tropisetron was administered intrathecally at 100 μg and 150 μg dosages. Behavioral tests were assessed before administration. Fifteen minutes after injection, behavioral tests were repeated. Randall-Sellitto and plantar test was used for mechanical and thermal hyperalgesia, respectively. Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…; Nasirinezhad et al . ). This shift from antinociception to pronociception may be mediated by the enhanced activation of 5‐HT receptor subtypes, which are pronociceptive, for example, the 5‐HT3R (Ali et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Nasirinezhad et al . ). This shift from antinociception to pronociception may be mediated by the enhanced activation of 5‐HT receptor subtypes, which are pronociceptive, for example, the 5‐HT3R (Ali et al .…”
Section: Discussionmentioning
confidence: 97%
“…At least half of the RVM neurons projecting to the spinal cord contain 5-HT (Skagerberg and Bjorklund 1985;Jones and Light 1992). These neurons were initially considered to have antinociceptive effects and later pronociceptive effects (Bourgoin et al 1980;Rivot et al 1982;Song et al 1999;Nasirinezhad et al 2016). This shift from antinociception to pronociception may be mediated by the enhanced activation of 5-HT receptor subtypes, which are pronociceptive, for example, the 5-HT3R (Ali et al 1996;Zeitz et al 2002;Guo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized clinical trial, Mei et al reported that a single-dose intravenous administration of tropisetron significantly alleviates early postoperative pain in women undergoing gynecological laparoscopies compared with those receiving placebo [43]. Likewise, Intrathecal administration of tropisetron in rats with spinal cord injury, decreased hyperalgesia and mechanical allodynia [44].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacotherapy holds the base of current treatment with little influence on functional recovery with only 30-40% decrease in neuropathic pain symptoms (Finnerup et al, 2005;Backonja et al, 2006). Besides, numerous medication adverse side effects are the major obstacles for the long-term use (Marineo et al, 2012;Hosseini et al, 2014;Nasirinezhad et al, 2015a). Motor dysfunction and neuropathic pain will persist unless the injured region recovers or pain control pathways reinforce.…”
Section: Introductionmentioning
confidence: 99%